Total synthesis, cytotoxic effects of damnacanthal, nordamnacanthal and related anthraquinone analogues - Akhtar, Muhammad Nadeem; Zareen, Seema; Yeap, Swee Keong; Ho, Wan Yong; Lo, Kong Mun; Hasan, Aurangzeb; Mohammed Alitheen, Noorjahan Banu (MDPI, 2013)
Naturally occurring anthraquinones, damnacanthal (1) and nordamnacanthal (2) were synthesized with modified reaction steps and investigated for their cytotoxicity against the MCF-7 and K-562 cancer cell lines, respectively. Intermediate analogues 2-bromomethyl-1,3-dimethoxyanthraquinone (5, IC 50 = 5.70 ± 0.21 and 8.50 ± 1.18 μg/mL), 2-hydroxymethyl-1,3-dimethoxyanthraquinone (6, IC50 = 12.10 ± 0.14 and 14.00 ± 2.13), 2-formyl-1,3-dimethoxyantharquinone (7, IC 50 = 13.10 ± 1.02 and 14.80 ± 0.74), 1,3-dimethoxy-2-methylanthraquinone (4, IC50 = 9.40 ± 3.51 and 28.40 ± 2.33), and 1,3-dihydroxy-2-methylanthraquinone (3, IC 50 = 25.60 ± 0.42 and 28.40 ± 0.79) also exhibited moderate cytotoxicity against MCF-7 and K-562 cancer cell lines, respectively. Other structurally related compounds like 1,3-dihydroxyanthraquinone (13a, IC50 = 19.70 ± 0.35 and 14.50 ± 1.28), 1,3-dimethoxyanthraquinone (13b, IC50 = 6.50 ± 0.66 and 5.90 ± 0.95) were also showed good cytotoxicity. The target compound damnacanthal (1) was found to be the most cytotoxic against the MCF-7 and K-562 cancer cell lines, with IC50 values of 3.80 ± 0.57 and 5.50 ± 1.26, respectively. The structures of all compounds were elucidated with the help of detailed spectroscopic techniques.